Oxidations with bonded salen-catalysts in microcapillaries - Sandel, Simone; Weber, Sven K.; Trapp, Oliver (Chemical engineering science, 2012)
Chiral vanadium(IV)-salen complexes with variable spacer length were immobilized on polysiloxanes, which were used as catalytically active stationary phase in on-column reaction gas chromatography, on-column reaction electrophoresis, in flow-through reactors and as coating of laboratory glassware. These devices modified with the catalytically active stationary phase were employed in asymmetric sulfoxidations using hydrogen peroxide as the oxidant. The here presented approach combines catalysis and chromatographic analysis in a single step and allows to study the kinetics of reactions and to optimize reaction conditions. The initial reaction kinetics and enantioselectivity of the sulfoxidation of benzylphenylsulfide was studied in dependency of the spacer length of the immobilized salen ligand. A drastic influence of the spacer length on the enantioselectivity in the here investigated sulfoxidation was measured.
Available online 18 October 2011
Gesehen am 16.08.2018